Integration of Islamic principles in modern science: its philosophy and method - Ahmed Shogar, Ibrahim Adam (IIUM Press, 2014)
The scientific discourse of Muslim intellectuals during the last century was mainly about the contemporary body of knowledge which introduced by Western civilization. While many Muslim thinkers were suspicious about the modern science, due to various aspects of cultural, ideology, and social elements that infused by Western civilization; the others were eager to face the challenge with an open mind. Islamization and Integration of knowledge, which have introduced as mission by the International Islamic University Malaysia (IIUM) provides good example of the later group. The idea of “Integration” reflects a profound grasp of epistemological challenges confronting the contemporary Muslim community. The concepts have been used as an epistemological approach in the prevailing discourse of Muslim intellectuals in the course of last three decades. The simple aim of Islamization and integration of knowledge is to remove the intellectual confusion created in Muslim mind by secular elements that have been infused and amalgamated into the body of contemporary knowledge.